Modulation of Intestinal Barrier Function and Wnt/β- Catenin Pathway by Sanzi Formula in Colorectal Adenoma Development - Peng, Wanqiu; Li, Zhongyi; Zou, Shuting; Li, Hui; Tian, Yaozhou; Hua, Yongzhi; Wei, Lanfu; Zhang, Zhenhai; Gu, Yi; Xu, Tingting (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Colorectal adenoma is a high-risk precursor lesion of colorectal cancer. Sanzi formula (SZF), a traditional Chinese medicine compound for the treatment of this disease, inhibits the growth of colorectal adenomas. This study aimed to investigate the mechanism by which SZF blocks the growth of colorectal adenomas in Apcmin/+ mice. Materials and Methods: C57BL/6J mice were used as the control group and were fed a normal diet. To create the colorectal adenoma model, Apcmin/+ mice were fed high-fat chow. Each administration group was given the appropriate drug by gavage at the same time as the modeling. The body weight, adenoma size, and adenoma number of mice in each group were recorded, and the colorectal tissue was subjected to HE staining and histopathological evaluation. The effect of SZF on inflammatory factors, tight junction (TJ) proteins, pathway proteins, and mRNA content in colorectal adenoma was examined by enzyme-linked immunosorbent assay, western blotting, immunofluorescence analysis, and quantitative real-time polymerase chain reaction. Results: The results showed that all dose groups of SZF improved the size, number, and histopathological damage of adenomas. All dose groups of SZF resulted in lower inflammatory factors, higher levels of TJ proteins, and lower levels of pathway proteins and mRNA. Particularly, the high-dose group of SZF was more effective. Conclusion: Sanzi formula interfered with the progression of colorectal adenoma in Apcmin/+ mice by repairing the intestinal barrier function and blocking the Wnt/β-catenin signaling pathway, which provided a new idea and scientific basis for clinical treatment. Cite this article as: Peng W, Li Z, Zou S, et al. Modulation of intestinal barrier function and wnt/β-catenin pathway by sanzi formula in colorectal adenoma development running head: SZF inhibits colorectal adenoma development. Turk J Gastroenterol. 2025;36(9):547-555.